Tecnica Quirurgica Esplenectomia En Canino Macho Durante La Pasantía En Una Clínica Veterinaria En Bogotá (2023)
PRADO VET S.A.S located in the city of Bogotá, in the town of Prado Summer. Its work team has high-quality professionals, where They specialize in the area of ​​small species. According to the above, the clinical practice was carried out under the theoretical knowledge practical, acquired at the Antonio Nariño University, in the company of the coordinator technician Dr. Neira German, surgery specialist at PRADO VET S.A.S.